Protein elicitor PeVn1 induces resistance to Botrytis cinerea in strawberry and differential transcriptomic analysis - Zhang, Ziyu; Wang, Dong; Wang, Yu; Dong, Baozhu; Hao, Jianxiu; Zhou, Hongyou (Frontiers in Microbiology, 2025)
Botrytis cinerea is one of the most destructive diseases in strawberry cultivation. The protein elicitor PeVn1 is a secreted protein produced by Verticillium nonalfalfae, and it has been shown to enhance plant resistance against fungal infections. However, the mechanisms by which the protein elicitor acts remain poorly understood. In this study, we conducted physiological, biochemical, and transcriptomic analyses on strawberry leaves to reveal the resistance conferred by PeVn1 against B. cinerea infection. PeVn1 treatment significantly reduced lesion areas on B. cinerea-infected strawberry leaves. During the infection period, PeVn1 increased the activities of various antioxidant and defense-related enzymes, thereby enhancing the plant’s oxidative capacity. Compared to inoculation with B. cinerea alone, malondialdehyde (MDA) and electrical conductivity levels were significantly reduced. Transcriptomic analysis identified a total of 277 differentially expressed genes (DEGs) in the leaves treated with PeVn1 compared to the control group. The three most enriched KEGG pathways were the MAPK signaling pathway, plant hormone signal transduction, and plant-pathogen interaction, all of which are associated with plant immunity. DEGs associated with plant-pathogen interaction pathways included Calmodulin-like protein 1, Calcium-dependent protein kinase, and Chitin elicitor receptor kinase 1-like protein. DEGs linked to MAPK and hormone signaling pathways included EIN3-3, ethylene-responsive transcription factor 1, MAPK9 (MKK9), and transcription factor WRKY42. These genes play critical roles in PAMP-triggered immunity (PTI) and effector-triggered immunity (ETI). They support the plant’s hypersensitive response (HR), cell wall reinforcement, and other defense mechanisms. In summary, the protein elicitor PeVn1 activates the MAPK signaling pathway, increases calcium ions, and stimulates the ethylene signaling pathway in strawberry leaves, thereby enhancing plant resistance to infection. The results demonstrate that PeVn1 has significant potential to improve resistance against fungal diseases in strawberries.